1970
DOI: 10.1161/01.res.26.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Plasma Peptides to the Myocardial Depressant Factor in Hemorrhagic Shock in Cats

Abstract: The pathophysiological relationships of a myocardial depressant factor (MDF) present in the plasma of cats in hemorrhagic shock were studied. Aprotinin (Trasylol), an inhibitor of a variety of proteases including kallikrein and trypsin, prolonged survival of cats in postoligemic shock as well as prevented the appearance of MDF in the plasma. Trasylol did not alter the arterial blood pressure, venous pressure, or heart rate of these cats in shock, nor did it protect by exerting a positive inotropic effect. Tras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1971
1971
1979
1979

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…21 This agent antagonizes a variety of proteases including trypsin, plasmin, and kallikrein. 22 Since aprotinin reduces bradykinin concentration as it protects in shock, 23 it thus renders less likely the bradykinin-potentiating effects of SQ 14,225 as being a significant component of its protective effect in hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 This agent antagonizes a variety of proteases including trypsin, plasmin, and kallikrein. 22 Since aprotinin reduces bradykinin concentration as it protects in shock, 23 it thus renders less likely the bradykinin-potentiating effects of SQ 14,225 as being a significant component of its protective effect in hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The reductions in lysosomal and proteolytic activities probably result from direct biochemical actions of SQ 14,225, since in vitro studies demonstrated lysosomal stabilization and general antiprotease actions. MDF is thought to be formed from a combination of the actions of lysosomal and zymogenic proteases within pancreatic acinar cells; 21 therefore, the lowered levels of this toxic peptide probably also are dependent on stabilization of lysosomal membranes and the antagonism of zymogenic proteases within pancreatic acinar cells.…”
Section: Discussionmentioning
confidence: 99%
“…The erythrocyte volume fraction before and after 2 h of ischemia was almost the same, indicating that no large volume of plasma could have been lost to the extravascular space. Lefer and Martin [15] demonstrated that a myocardial depressant factor was released from ischemic splanchnic tissue and assumed this fac tor to be a polypeptide. Williams et al [27] observed a myocardial de pressant factor in dog plasma after occlusion of the arteries of a small in testinal segment.…”
Section: H Of Intestinal Ischemiamentioning
confidence: 99%
“…L efer et al [15] and L efer and M artin [16] have recently presented evidence which suggests that a low molecular weight protein breakdown product is elaborated during shock that is toxic to the myocardium. It has been hypothesized that this material is the result of the action of proteases released from ischemic pancreas on proteins in the blood.…”
mentioning
confidence: 99%